A CRITICAL REVIEW OF INGUDI (BALANITES AGEYPTIACA LINN. DELILE) FROM KOSHA AND NIGHANTUS - Sanjeev, *Kumar; Kamal Nayan, Dwivedi (AYUSHDHARA, 2015)
Ingudi (Balanites aegyptiaca Linn. Delile) known as ‘Desert Date’ is a small evergreen tree. Man, the superior most of all species has always been remaining in a search of One Prime Goal: “The perfect health”. From Vedic era to space age, all the researches have been directed by the eminent scholars to achieve the same. The Nighantus, Ayurvedic form of Materia Medica could help significantly in this direction. Numerous Nighantus have been written from the very beginning of Ayurvedic period to solve the hidden meanings of cryptic names of medicinal plants. It is believed that at the end of each Samhita a Nighantu was there. In this work a Nighantu of Sushruta named Sausruta Nighantu and another by Vagbhata the Astanga Nighantu are discussed. The present work aims to discuss Ingudi in various Nighantus as manuscripts or just as evidence - in a chronological order.